Identification of Interleukin (IL)-33 Inhibitory Constituents from Canavalia gladiata Pods - Le Ba Vinh; Seung Hyuck Shin; Yoo Kyong Han; Young Jun Kim; Nguyen Cao Cuong; Soohwan Oh; Ki Yong Lee (MDPI AG, 2024)
Interleukin (IL)-33, a member of the IL-1 cytokine family, plays a vital role in immune system regulation and inflammation, with oxidative stress being implicated in its expression. During the search for compounds from natural sources with potential as therapeutic agents for allergic diseases via IL-33 signal modulation, we discovered significant IL-33 inhibitory activity in the methanol extract of Canavalia gladiata (sword bean) pods. Through chromatographic separation and liquid chromatography-mass spectrometry, we isolated 11 compounds (1-11) from the methanol extract. Furthermore, we assessed the inhibitory effects of these substances on IL-33/ST2 signaling in processes related to inflammatory and autoimmune diseases using an enzyme-linked immunosorbent assay. Among them, compounds 7, 10, and 11 exhibited substantial IL-33 inhibitory efficacy, with values reaching 78%, 86%, and 79% at 100 µM, respectively. Remarkably, compounds 7, 10, and 11 demonstrated significant and dose-dependent inhibition of IL-33 signaling at concentrations of 10, 50, and 100 µM. Computational molecular docking and dynamic simulations further elucidated the underlying mechanisms. These findings have promising pharmacological implications for allergy prevention and treatment associated with flavonoid glycosides derived from C. gladiata.